Improving Airport On-Time Performance Using Kepner-Tregoe Problem-Solving Approaches - Gita Kurnia; Hegel Johanes; Dicka Hidayat; Adelady Rozha; Mutia Zahvira; Iwan Sukarno (JURNAL TEKNOLOGIA, 2020)
Indonesia’s Soekarno-Hatta Airport has been putting efforts to provide a better service to airline passengers. However, due to some problems, Soekarno-Hatta Airport's on-time performance has recorded a drastic decline since the beginning of 2016 to early 2018. Therefore, this study aims to propose a strategy to improve Soekarno-Hatta Airport’s on-time performance using creative problem-solving approaches. The proposed strategy is designed based on secondary data collected from January 2016 to December 2018. This study evaluates the data using creative problem-solving approaches and uses Singapore’s Changi Airport as a benchmark airport. The root causes of improving on-time performance is identified using Kepner-Tregoe Problem Analysis, while the solution is designed using SCAMPER technique, Kepner-Tregoe Decision Analysis, Adverse Consequences table and Kepner-Tregoe Potential Problem Analysis. The result reveals several problem’s root causes which influence the low on-time performance in Soekarno-Hatta Airport such as: less integrated baggage handling system, longer passenger loading process due to long queue at check-in gates, high number of arriving delay caused by late departure from origin port, and unpredictable weather. The proposed solution for these problems is improving the baggage handling system in Soekarno-Hatta Airport using the latest conveyor technology. By implementing this solution, it is expected that the on-time performance in Soekarno-Hatta Airport will increase and reach the same level as Changi Airport’s.